The Relationship Between Ship Space, Vector Presence, and Sanitation Food and Processing Waste to Sanitation Ships Anchored at Tobelo Port - yunus, Malik; Dadere, Engganis; Tahulending, Jane (JURNAL BIOS LOGOS, 2025)
The aim of the research is to analyze the connection between the condition of the room on the ship, the existence of vectors, the sanitation of food, and the processing of waste to level the sanitation of ships anchored at Tobelo Port. The type of research uses an analytic observational design with a cross-sectional approach. The population study is all over the anchored ship​ during the period of research, with samples taken according to the criteria of eligibility, inspection, and sanitation of the ship. Data collected through observation, interviews, and assessment checklists of sanitation boats based on guidelines of the Ministry of Health of the Republic of Indonesia. Data analysis was carried out in a univariate and bivariate way using the chi-square test. The results of the study show that there is a significant relationship​ between condition room ships (p<0.05), presence of vectors (p<0.05), food sanitation (p<0.05), and waste processing (p<0.05) and the level of sanitation on the ship. The ship is in clean condition, has a free room​ vector, has management of hygienic food, and has good waste processing, showing an adequate mark for sanitation​ and a healthy environment on the ship. In conclusion, the internal factors of the ship, like room, control vectors, sanitation food, and systems processing waste, play an important role in guarding the sanitation of the ship. Required improvement supervision and routine guidance by officers of the health harbor ensure every anchored ship​ fulfills the established standard of sanitation.​